REVIEW OF ALUMINA IN ADSORPTION PROCESSES FOR EMERGING POLLUTANTS - Terrazas, Karem Arely Aguirre; Nahúm, Medellín-Castillo; Baltazar, Álvaro de Jesús Ruíz; Pérez, onatan Torres; López, Simón Yobanny Reyes (International Journal of Research -GRANTHAALAYAH, 2021)
Water pollution can be found in the oceans, seas, rivers and lakes which can be taken as organic pollutants or better known as emerging pollutants. Emerging pollutants (EP´s) are chemical substances that persist in the environment, these molecules are in the food chain causing risks and adverse effects for human health and the environment. EP´s are not they are discharged as effluents indiscriminately, for this reason is important to improve water treatment by the application of advanced techniques as adsorption. Adsorbents like alumina are known for their large surface area, high mechanical properties and good resistivity to thermal degradation. Aluminum oxide or alumina (Al2O3) is a solid white ceramic material which has been considered an efficient adsorbent for EP´s removal as advanced water treatment.